A Convenient HPLC Method for Detection of Okadaic Acid Analogs as 9-Anthrylmethyl Esters with Automated Sample Cleanup by Column Switching. (27th November 2019) - Uchida, Hajime; Watanabe, Ryuichi; Matsushima, Ryoji; Uchida, Naoyuki; Nagai, Hiroshi; Kamio, Michiya; Murata, Masakazu; Yasumoto, Takeshi; Suzuki, Toshiyuki
Abstract: A convenient HPLC-fluorometric detection (FLD) method for okadaic acid (OA) analogs as 9-anthrylmethyl esters was developed with the addition of column switching to simplify and automate cleanup. Methanol extracts of shellfish were first treated to hydrolyze OA esters and then reacted with 9-anthryldiazomethane (ADAM). ADAM derivatives of OA and dinophysistoxin-1 (DTX1) were subsequently determined by HPLC-FLDfollowing automated column-switching cleanup. The LOD (S/N = 3) and LOQ (S/N = 10) of OA and DTX1 obtained from bivalves fortified with toxin in our methodwere approximately 2.6 and 8.6 ng/g whole meat, respectively. The recoveries of OA and DTX1 at all fortification levels of bivalve extracts ranged from 90 to113%, with RSD values of 0.9–9.9%. The new method is applicable to the routine monitoring of OA analogs as an inexpensive and convenient alternative to HPLC/MS.